A Study on Relationship Between Perceived Discrimination and Performance Management System: A Case Study of a Financial Institution in Malaysia - Mohamed Safuan, Mohamed Taib (2012)
Managing workforce performance is a goal-oriented process to maximise the productivity of employees and is a critical aspect of organizational effectiveness. However, relatively limited research has been conducted on the relationship between Performance Management system and discrimination especially in Malaysia. The purpose of this study is to examine the relationship between Performance Management System and discrimination in a financial institution. Data were collected from 64 respondents and analysed through questionnaires. The result was being analyzed by using Statistical Package for Social Science (SPSS) version 19. From the data analysed, the result revealed that the independent variable (discrimination) have negative correlations with dependent variable (performance management system). The findings, recommendations and implication for future research were also discussed.